Travels on the squark-gluino mass plane - Jaeckel, Joerg; Khoze, Valentin V.; Plehn, Tilman; Richardson, Peter (Physical review. D, Particles, fields, gravitation, and cosmology, 2012)
Soft supersymmetry breaking appears in the weak-scale effective action but is usually generated at higher scales. For these models the structure of the renormalization group evolution down to the electroweak scale leaves only part of the squark-gluino and slepton-gaugino mass planes accessible. Our observations divide these physical mass planes into three wedges: the first can be reached by all models of high-scale breaking; the second can only be populated by models with a low mediation scale; in the third wedge squarks and gluinos would have to be described by an exotic theory. All usual benchmark points reside in the first wedge, even though an LHC discovery in the third wedge would arguably be the most exciting outcome.
Gesehen am 20.04.2018